Weeds Associated with Papaya Plants (Carica Papaya L.) in Bengkulu - Nia Kurniati Marpaung; Mimi Sutrawati; Ridha Rizki Novanda; Dwi Wahyuni Ganefianti; Tunjung Pamekas (Badan Penerbitan Fakultas Pertanian (BPFP), 2022)
Papaya crops associated with weeds are commonly found in Kepahiang and Rejang Lebong district, Bengkulu. The presence of weeds can affect the development and productivity of papaya. Until now, the species and diversity of weeds associated with papaya crops have not been reported. This study aimed to identify and determine weed density around papaya crops. Sampling was conducted to measure and calculate weed density using the quadratic method measuring 1 m x 1 m. The data collection was done by randomly taking the weeds on the plots at as many as 10 points. Based on the result of weed identification, there were 16 species of weeds spread over 9 families. The calculation of the highest relative density in Padang Lekat, Durian Depun Village, and Dua Jalur Road was Ageratum conyzoides (0,584%), Claytonia perfoliata (0,306%), and Eleusine indica (0,274%).